2021
DOI: 10.3389/fnagi.2021.698184
|View full text |Cite
|
Sign up to set email alerts
|

Dementia as Risk Factor for Severe Coronavirus Disease 2019: A Case-Control Study

Abstract: BackgroundThe aim of the present study was to investigate the outcome of patients with SARS-CoV-2 infection and dementia.Patients and MethodsIn a multicenter, observational, 1:2 matched case-control study all 23 patients with a history of dementia, hospitalized with a diagnosis of SARS-CoV-2 infection from February 28th 2020 to January 31st 2021 were enrolled. For each Case, 2 patients without dementia observed in the same period study, pair matched for gender, age (±5 years), PaO2/FiO2 (P/F) ratio at admissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…Pisaturo et al [88] reported that patients with a previous diagnosis of dementia were more vulnerable than matched control patients without dementia and at increased risk of severe COVID-19 and consequent death.…”
Section: Sars-cov-2 Infection and Psychiatric Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…Pisaturo et al [88] reported that patients with a previous diagnosis of dementia were more vulnerable than matched control patients without dementia and at increased risk of severe COVID-19 and consequent death.…”
Section: Sars-cov-2 Infection and Psychiatric Outcomesmentioning
confidence: 99%
“…Indeed, preexisting cognitive impairment might also represent a significant predisposing factor for the onset of delirium [92,93] (Table 1). Pisaturo et al [88] reported that patients with dementia are at increased risk of severe COVID-19 and consequent death. Dementia is an insidious neurodegenerative condition, characterized by a chronic and progressive cognitive decline of performance in one or more cognitive domains, interfering with independence in everyday activities.…”
Section: Precipitating Factorsmentioning
confidence: 99%
“…Besides risk factors, dementias and COVID-19 might share comorbidities such as hypertension, diabetes, and obesity, most of which are associated with an overactive renin-angiotensin system, cerebrovascular dysfunction and neuroinflammation ( 12 ). The study of Pisaturo et al ( 37 ) reveals that patients with a previous diagnosis of dementia were more vulnerable than matched control patients without dementia, plus at increased risk of severe COVID-19 and consequent death.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of clinical manifestations and outcomes of COVID-19 have been reported, from asymptomatic and mild respiratory infections to pneumonia and acute respiratory distress syndrome (ARDS), as well as life-threatening multiple organ failure [2]. Several studies have highlighted the impact of different risk factors, such as being aged over 65, diabetes, hypertension, chronic kidney disease, dementia, and active cancer, all of which contribute to increased mortality and need for non-invasive and invasive ventilation [3][4][5][6][7]. The identification of clinical and biochemical factors potentially associated with severe COVID-19 is of paramount importance, and may help healthcare professionals to personalize treatment, especially in the current era of early effective treatment, i.e., antivirals and monoclonal antibodies, according to the risk factors of each subject, as well as to allocate proper resources at all levels of care.…”
Section: Introductionmentioning
confidence: 99%